Crop diversity induces trade-offs in microbial biopesticide susceptibility that could delay pest resistance evolution. - Rosie M Mangan; Matthew C Tinsley; Ester Ferrari; Ricardo A Polanczyk; Luc F Bussière (PLoS Pathogens)
Pathogens often exert strong selection on host populations, yet considerable genetic variation for infection defence persists. Environmental heterogeneity may cause fitness trade-offs that prevent fixation of host alleles affecting survival when exposed to pathogens in wild populations. Pathogens are extensively used in biocontrol for crop protection. However, the risks of pest resistance evolution to biocontrol are frequently underappreciated: the key drivers of fitness trade-offs for pathogen resistance remain unclear, both in natural and managed populations. We investigate whether pathogen identity or host diet has a stronger effect on allelic fitness by quantifying genetic variation and covariation for survival in an insect pest across distinct combinations of fungal pathogen infection and plant diet. We demonstrate substantial heritability, indicating considerable risks of biopesticide resistance evolution. Contrary to conventional thinking in host-pathogen biology, we found no strong genetic trade-offs for surviving exposure to two different fungal pathogen species. However, changes in plant diet dramatically altered selection, revealing diet-mediated genetic trade-offs affecting pest survival. Our data suggest that trade-offs in traits not strictly related to infection responses could nevertheless maintain genetic variation in natural and agricultural landscapes.